Anterior prefrontal brain activity during emotion control predicts resilience to post-traumatic stress-symptoms - Kaldewaij, Reinoud (Nat Hum Behav, 2021)
Regulating social emotional actions is essential for coping with life stressors and is associated with control by the anterior prefrontal cortex (aPFC) over the amygdala. However, it remains unclear to what extent prefrontal emotion regulation capacities contribute to resilience against developing post-traumatic stress disorder (PTSD) symptoms. Here, 185 police recruits who experienced their core trauma in the line of duty participated ina prospective longitudinal study. Pre-and post-trauma, they performed a well-established functionalMRI approach-avoidance task, mapping impulsive and controlled emotional actions. Higher baseline aPFC, dorsal and medial frontal pole activity was related to lower PTSD-symptoms after trauma exposure.aPFC activity predicted symptom development over and above self-reported and behavioral measures. Trauma-exposure, but not trauma-symptoms, predicted amygdala activation at follow-up. These findings suggest that prefrontal emotion regulation activity predicts increased resilience against developing post-traumatic stress symptoms, and may provide fruitful starting points for prediction and intervention studies.